ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KECURANGAN LAPORAN KEUANGAN DALAM PERSPEKTIF FRAUD PENTAGON - Sohada, Novia Nor; Tanusdjaja, Hendang (Jurnal Paradigma Akuntansi, 2024)
The purpose of this study is to analyze the factors that influence financial statement fraud pentagon. The sample of this study 150 observation seen from 50 manufacturing companies listing in Indonesia Stock Exchange period 2019-2021. The type of data used is secondary data, which is an annual report of companies listing in the IDX for period 2019-2021. Hypothesis test used with multiple linear regression method with SPSS software, whare previously the classical principle test for the feasibility of research data. The results of this study indicate that study indicate that external pressure as measured by the leverage ratio, which has a significant effect on financial statement fraud. Ineffective monitoring as measured by the ratio of independen commissioners (BDOUT), change in auditor as measured by changes in independent auditors, has no significant effect on financial statement fraud.